2021
DOI: 10.1177/09735984211050691
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Willingness to Receive COVID-19 Vaccine Among Adults: A Cross-sectional Study in Bangladesh

Abstract: The COVID-19 vaccine has been made available for emergency use in Bangladesh. However, willingness to receive the vaccine may be affected by varying factors across the country. Therefore, this study aimed to investigate the factors that influence willingness to receive the vaccine among Bangladeshi adults. A population-based cross-sectional online survey was conducted among a sample of 1,725 Bangladesh adults (age 18 years and older). The statistical analysis included univariate, bivariate and multivariate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
3
11
0
1
Order By: Relevance
“…The findings are supported by a prior study showing that the COVID-19 vaccine acceptance rate was 41.8% in Thailand (31). A previous study conducted in Bangladesh revealed that 85% of the population had an intention to vaccinate (32). Another study in the United Kingdom and United States showed that 54.1% of respondents would accept a COVID-19 vaccine to protect themselves against the infection (33).…”
Section: Discussionsupporting
confidence: 75%
“…The findings are supported by a prior study showing that the COVID-19 vaccine acceptance rate was 41.8% in Thailand (31). A previous study conducted in Bangladesh revealed that 85% of the population had an intention to vaccinate (32). Another study in the United Kingdom and United States showed that 54.1% of respondents would accept a COVID-19 vaccine to protect themselves against the infection (33).…”
Section: Discussionsupporting
confidence: 75%
“…While avoiding crowded places is a key COVID-19 intervention strategy, it was observed in our study that there was less inclination to avoid crowded places than what was reported in a similar study done in the Netherlands (76). The majority (82.5%) of participants in this study were willing to receive the COVID-19 vaccine, which was identical to observations reported in Lebanon (77), Bangladesh (78), China (55), and the Philippines (79). It is envisaged that increased vaccine acceptance may help increase vaccinations across the globe (80).…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have identified the key predictors of COVID-10 vaccine acceptance and reported several factors that would affect the outcome variable including, age, 5 , 8 10 educational level, 5 , 7 , 10 Occupation, 5 Gender, 5 , 11 knowledge, 11 having a chronic disease, 11 , 12 and residence. 13 …”
Section: Introductionmentioning
confidence: 99%